PENGARUH TERPAAN IKLAN SHOPEE FOOD TERHADAP MINAT BELI REMAJA DI DENPASAR - Prayoga, Dimas Eza; Gelgel, Ni Made Ras Amanda; Suryawati, I Gusti Agung Alit (E-Jurnal Medium, 2023)
Advertising becomes important for companies where advertising can produce work that will later become a high income. Creative advertising is an advertisement that is ori and there is no element of similarity with other advertisements, advertisements that we did not expect, advertisements that we did not expect, advertisements that have meaning or meaning, and advertisements that can affect our emotional level (Swastha, 2000). This research explains how the influence of Shopee Food advertising on the buying interest of teenagers in Denpasar. This research uses explanatory quantitative methods. The number of samples in this study was 72 respondents. The respondents in this study were teenagers in Denpasar city with an age range of 18 to 23 years. Researchers used a simple linear regression statistical test to prove and analyze the data. Data analysis using SPSS Statistical 24 program. The results showed a variable relationship between Shopee Food advertising exposure and teenagers' buying interest in Denpasar. With a coefficient of determination (R Square) of 0.537. These results show that the influence of Shopee Food advertising on the buying interest of teenagers in Denpasar is 53.7%. Keywords: Ad Exposure, Shopee Food, Buying Interest